"I dare with new technologies, how about you?" (Journal of Parents and Teachers, 2014)
The New Information and Communication Technologies (ICTs) are resources that are increasingly found in our society; however, these are not accessible to everyone, creating situations of digital and social exclusion. Therefore, it is essential to propose digital leisure workshops that bring technologies to the entire population and to the characteristics of the group in question, counting on their habits and interests for their proper development. Being the participation voluntary and accessible to all people who want to register, without commitment and without any level of prior knowledge.
Keywords: ICT; digital workshops; leisure; digital exclusion; digital divide; literacy; habits